Wild Things: Manufacturing Desire in the Urarina Moral Economy. (19th February 2013) - Walker, Harry
Abstract: Drawing on the case of the Peruvian Urarina, this article seeks to understand the present high demand for Western trade goods among native Amazonian peoples by situating it within a broader economy of desire with roots in historical experiences of colonization. The relations of "taming" that have long been a feature of encounters with outsiders, mediating an opposition between "savage" and "civilized" states, have become a central part of the caring dynamic between husbands and wives. This is increasingly focused on the provision of commodities, which are construed as akin to wild pets in need of taming and whose acquisition is a quintessentially male pursuit, much like hunting. While exacerbating existing gender asymmetries, this process points to gender as a key point of articulation between the subsistence economy and a penetrating market, and exemplifies the "decoding" effects of capitalism, through which spheres of exchange are conflated and desires intensified.